Social interaction as an indicator of learning difficulties for children Kindergarteners with deficiencies in scholastic skills (Journal of the College of Basic Education, 2022)
This research sought to find out the ability of social interaction to predict learning difficultiesKindergarten children with deficiencies in pre-school skills; the research sample was (147) childrenFrom the preparatory class children, the researcher used the social interaction test and prepared a testpre-school skills, and the researcher extracted its validity and reliability, and the research concluded that there are (44)Children with deficiencies in pre-school skills, which are represented by deficiencies in recognitionNumbers and letters among (18) children, and deficiency in phonological perception among (11) children(15) children suffered from deficiencies in recognizing objects and letters, and it appeared in the search results that:Pre-school skills contribute (65.5%) to social interaction.